OBSERVATION OF THE STARK-EFFECT IN AUTOIONIZING RYDBERG STATES OF MOLECULAR-HYDROGEN - Fielding, H; Softley, T (1991)
The dc Stark effect is studied for autoionising Rydberg states of H2 converging on the ν+=2 ionisation limit. The levels (n = 13-22) are excited from the ground state using a coherent XUV source (bandwidth ≈ 1 cm-1) and are strongly perturbed by the field (15-2000 V/cm). Many new states are observed, including the high-/hydrogenic manifolds. A detailed Stark map is obtained for the first time, and a matrix diagonalisation calculation of field-induced state mixing is carried out to explain some of the observed features. © 1991.